Speech By Brig. Jen. Dato’ Prof. Dr. Kamarudin Hussin Vice Chancellor of UniMAP for Closing Ceremony i-Envex 2011 - Kamarudin, Hussin, Brig. Jen. Dato’ Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
Closing Ceremony for International Engineering Invention and Innovation Exhibition (i-ENVEX) 2011 was held on 10th April 2011 at 2020 Hall, Kangar, Perlis.